Some novel effects in superconducting nanojunctions: Сверхпроводимость и мезоскопические структуры - Zaikin, Andrei D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
In this paper we address several new developments in the theory of dc Josephson effect in superconducting weak links. We analyze an interplay between quantum interference effects and Andreev reflection in SNS nanojunctions with insulating barriers and demonstrate that these effects may qualitatively modify the Josephson current in such structures. We also investigate an impact of the parity effect on persistent currents in superconducting nanorings interrupted by a quantum point contact (QPC). In the limit of zero temperature and for the odd number of electrons in the ring we predict complete suppression of the supercurrent across QPC with one conducting mode. In nanorings with SNS junctions a p-state can occur for the odd number of electrons. Changing this number from even to odd yields spontaneous supercurrent in the ground state of such rings without any externally applied magnetic flux.